POLITICAL BRANDING ON INSTAGRAM OF YOUNG FEMALE POLITICIANTS IN INDONESIA - Alsira Novaega, Jiwan; Farni Syam Maella, Nur’annafi (Proceeding of International Conference on Multidisciplinary Research, 2024)
The rise of social media has transformed political communication, providing politicians with platforms to engage with constituents directly. This study explores the use of Instagram for political branding by young female politicians in Indonesia, focusing on strategies employed to maintain their incumbency and influence voter perceptions. Utilizing a qualitative approach, the research involves case studies of young female incumbent candidates for DPRD Surabaya, with a particular focus on Ning Juliana. Data was collected through content analysis of Instagram posts. Findings indicate that young female politicians leverage Instagram to craft personal and political narratives, emphasizing authenticity, engagement, and visual appeal. The strategic use of diverse content types ranging from personal stories to policy discussions enhances voter engagement and supports branding efforts. Challenges identified include maintaining consistent engagement, countering negative feedback, and navigating the blurred lines between personal and political content. The study highlights the importance of digital literacy and adaptive strategies in maximizing the potential of Instagram for political branding. The implications of this research extend to political campaigners, policymakers, and scholars interested in the intersections of gender, digital communication, and political participation. Recommendations are offered for optimizing Instagram use, addressing challenges, and fostering a supportive digital environment for female politicians. Future research should explore longitudinal impacts of social media branding on electoral success and voter behavior